Role magnesium in adult obese people with dyslipidemia a literature review - Casós-Portocarrero, Karla Luz del Rocío (2025)
Obesity contributes directly to dyslipidaemia due to various factors, one of which has been little studied: magnesium deficiency in obese people may be caused by a deficiency in magnesium intake. Hypomagnesaemia leads to various alterations such as: a diversion of the glucose pathway towards an increase in lipids, oxidative stress, an indirect activation of the NF-κB pathway resulting in insulin resistance and an increase in cholesterol. Research has shown an inverse relationship between magnesium levels and obesity. We conclude that hypomagnesaemia leads to insulin resistance and dyslipidaemias.